A Journal Dedicated to Social Equity and Public Administration - Mary Guy; Brian Williams (Journal of Social Equity and Public Administration)
Written by the coeditors-in-chief, this essay introduces the Journal of Social Equity and Public Administration (JSEPA) and situates it among other public administration journals. Its mission, aims, and scope are explained. Manuscripts are welcomed that identify and probe societal structures and dynamics that create or perpetuate inequity, or that overcome it. Published for a global audience, it is a theoretically and methodologically inclusive journal. Because social equity is a moving target, always evolving, the pages of this journal will reflect its course.